Juridical Analysis of the Constitutional Court's Decision Number 81/PUU-XXIII/2025 Rejecting the Formal Test of Law Number 3 of 2025 concerning Amendments to Law Number 34 of 2004 concerning the Indonesian National Army - Walidul Halim; Irwan Triadi (Catalist Indo Publisher, 2026)
Constitutional Court Decision Number 81/PUU-XXIII/2025, which rejected the formal judicial review of Law Number 3 of 2025 concerning the Amendment to Law Number 34 of 2004 on the Indonesian National Armed Forces (TNI), has sparked debate regarding the standards of law-making in a democratic rule-of-law state. This study analyzes the Court's legal reasoning in assessing the formal constitutionality of the TNI Law and examines its constitutional implications for the principles of due process of law, transparency, and meaningful public participation. This research employs a normative legal method using statutory, conceptual, and case approaches, focusing on an in-depth analysis of the Court's decision. The findings show that the Constitutional Court justified the legislative process by emphasizing the urgency of national defense policy and certain normative considerations, concluding that the planning, drafting, and deliberation stages formally complied with legal requirements. However, dissenting opinions from several Justices highlight procedural concerns, including the designation of the bill as a carry-over bill, revisions to the National Legislation Program (Prolegnas) without adequate evaluation, and the limited guarantee of meaningful public participation. Although the law was declared formally constitutional, the decision raises concerns about procedural flexibility that may weaken democratic legislative standards and affect the quality of constitutional governance in Indonesia.